The influence of hypoxia on platelet function and plasmatic coagulation during systemic inflammation in humans in vivo. (3rd October 2019) - Kiers, Dorien; Tunjungputri, Rahajeng N.; Borkus, Rowie; Scheffer, Gert-Jan; de groot, Philip G.; Urbanus, Rolf T.; van der ven, Andre J.; Pickkers, Peter; de Mast, Quirijn; Kox, Matthijs
Abstract: Systemic inflammation and hypoxia frequently occur simultaneously in critically ill patients, and are both associated with platelet activation and coagulopathy. However, human in vivo data on the effects of hypoxia on platelet function and plasmatic coagulation under systemic inflammatory conditions are lacking. In the present study, 20 healthy male volunteers were randomized to either 3.5 h of hypoxia (peripheral saturation 80–85%) or normoxia (room air), and systemic inflammation was elicited by intravenous administration of 2 ng/kg endotoxin. Various parameters of platelet function and plasmatic coagulation were determined serially. Endotoxemia resulted in increased circulating platelet–monocyte complexes and enhanced platelet reactivity, effects which were attenuated by hypoxia. Furthermore, endotoxin administration resulted in decreased plasma levels of platelet factor-4 levels and increased concentrations of von Willebrand factor. These endotoxemia-induced effects were not influenced by hypoxia. Neither endotoxemia nor hypoxia affected thrombin generation. In conclusion, our data reveal that hypoxia attenuates the endotoxemia-induced increases in platelet–monocyte formation and platelet reactivity, while leaving parameters of plasmatic coagulation unaffected.